Medicinal plants volume 2 - Gurib-Fakim, Ameenah; Schmelzer, G.H. (CTA / Backhuys Publishers / PROTA, 2013)
Liberally illustrated throughout, with geographical distribution maps and botanical line drawings, this is the second of four volumes dealing with medicinal plants of Tropical Africa. Here 409 plants are described in 146 review articles. A useful accompanying CD-ROM contains additional photos and allows for easy text searches.